Study on the improvements of body composition indices in adult women by means of aerobic gymnastics - Geanta, Vlad Adrian; Camenidis, Carmen Magdalena (Arena-Journal of Physical Activities, 2023)
Introduction: Fitness in relation to health is a contemporary topic, which is topical due to the diversity of methods and programmes to support and improve health and is increasingly being addressed by the sports and medical scientific community. Regular physical activity and exercise are the actuators of our whole body’s well-being, both somatic, functional, and cognitive. Purpose: Through this article, we wish to highlight the use of a personalized aerobic fitness program conducted collectively that can generate significant results based on transforming the perception of how participants look and feel good in their own bodies. Materials & Methods: The research sample consisted of nineteen young adult female subjects (N=19, age = 35,4 ± 5,02 years, Weight(i) 66,7 ± 12,61 kg, Height= 166 ± 6,69 cm) clients of a fitness center. They trained following a personalized program of an aerobic fitness class for 4 weeks, with a frequency of 2 workouts per week. The results indicate a significant improvement in the somatic parameters of the research participants, but in order to maintain the results obtained, physical activity should be continued after the end of the research. Conlusions: Within the limits of our study, we conclude that significant changes in body composition indices can be produced in adult women by performing an exercise routine under systematic and continuous conditions.